Miguel de Unamuno, Indalecio Prieto : correspondencia 1916-1934 / [prólogo, Mariano del Mazo de Unamuno ; estudio introductorio, Luis María Sala González] - Prieto, Indalecio (1883-1962) Unamuno, Mariano del M. deSala González, Luis María; Unamuno, Miguel de (1864-1936)
Bibliografía